Understanding profit margins of medical providers from prescription drugs: evidence from Taiwan - Liu, Ya-Ming (International health, 2020)
This study empirically estimates the magnitude and associated determinants of profit margins that medical providers earn from prescription drugs based on Taiwan's pharmaceutical market. Our main data set is from the population-based claims data compiled by the National Health Insurance Research Database covering three waves of price adjustment: July-December 2004, October 2007-September 2008 and October 2009-September 2010. Only drugs whose reimbursement prices were adjusted using the R-zone formula were used as samples for this study. By calculating the difference between retail and wholesale prices for 796 pharmaceutical products, we can estimate the profit margin determinants using the regression model. We found evidence that suppliers of generic drugs tend to offer larger discounts to medical providers than suppliers of brand-name drugs. In addition, the countervailing power of wholesale pharmaceuticals, as measured by the discount rate offered by pharmaceutical manufacturers, is positively associated with the degree of competition within the pharmaceutical market and the size of the market itself. Our findings imply that the profit-seeking behaviour exhibited by medical providers is the engine of competitive forces in Taiwan's prescription drug market. This creates financial incentives for them, which in turn influences their choices of prescription drugs.